The application of T1 and T2 relaxation time and magnetization transfer ratios to the early diagnosis of patellar cartilage osteoarthritis - Yao, Weiwu; Qu, Nan; Lu, Zhihua; Yang, Shixun (Skeletal radiology, 2009)
Objectives We compare the T1 and T2 relaxation times and magnetization transfer ratios (MTRs) of normal subjects and patients with osteoarthritis (OA) to evaluate the ability of these techniques to aid in the early diagnosis and treatment of OA. Materials and methods The knee joints in 11 normal volunteers and 40 patients with OA were prospectively evaluated using T1 relaxation times as measured using delayed gadolinium-enhanced MRI of cartilage (dGEMRIC), T2 relaxation times (multiple spin-echo sequence, T2 mapping), and MTRs. The OA patients were further categorized into mild, moderate, and severe OA. Results The mean T1 relaxation times of the four groups (normal, mild OA, moderate OA, and severe OA) were: 487.3 ± 27.7, 458.0 ± 55.9, 405.9 ± 57.3, and 357.9 ± 36.7 respectively ( p <0.001). The mean T2 relaxation times of the four groups were: 37.8 ± 3.3, 44.0 ± 8.5, 50.9 ± 9.5, and 57.4 ± 4.8 respectively ( p < 0.001). T1 relaxation time decreased and T2 relaxation time increased with worsening degeneration of patellar cartilage. The result of the covariance analysis showed that the covariate age had a significant influence on T2 relaxation time ( p < 0.001). No significant differences between the normal and OA groups using MTR were noted. Conclusion T1 and T2 relaxation times are relatively sensitive to early degenerative changes in the patellar cartilage, whereas the MTR may have some limitations with regard to early detection of OA. In addition, The T1 and T2 relaxation times negatively correlate with each other, which is a novel finding.